Engaging emergency clinicians in emergency department clinical research. Issue 3 (30th January 2018) - McRae, Andrew D.; Perry, Jeffrey J.; Brehaut, Jamie; Brown, Erica; Curran, Janet; Emond, Marcel; Hohl, Corinne; Taljaard, Monica; Stiell, Ian G.
Abstract: Objective: The objective of this panel was to generate recommendations to promote the engagement of front-line emergency department (ED) clinicians in clinical and implementation research. Methods: Panel members conducted semi-structured interviews with 37 Canadian adult and pediatric emergency medicine researchers to elicit barriers and facilitators to clinician engagement in research activities, and to glean strategies for promoting clinician engagement. Results: Responses were organized by themes, and, based on these responses, recommendations were developed and refined in an iterative fashion by panel members. Conclusions: We offer eight recommendations to promote front-line clinician engagement in clinical research activities. Recommendations to promote clinician engagement specifically address the creation of a research-friendly culture in the ED, minimizing the burden of data collection on clinical staff through the careful design of data collection tools and the use of research staff, and communication between researchers and clinical staff to promote adherence to study protocols. RÉSUMÉ: Objectif: Le groupe de travail avait pour but d'élaborer des recommandations visant à susciter l'intérêt des cliniciens de premier recours au service des urgences pour la recherche clinique et pour la recherche sur la mise en œuvre. Méthode: Les membres du groupe ont mené des entrevues semi-structurées avec 37 chercheurs canadiens en médecine d'urgence tant adulte que pédiatrique dans le but de faire ressortir les obstacles à l'intérêt des cliniciens pour les activités de recherche ainsi que les facteurs facilitants, et de glaner des stratégies visant à susciter leur intérêt. Résultats: L'équipe a groupé les réponses par thème, élaboré des recommandations en tenant compte des réponses reçues, puis amélioré ces recommandations selon un processus itératif. Conclusions: Le groupe présente huit recommandations visant à susciter l'intérêt des cliniciens de premier recours pour les activités de recherche clinique. Ces recommandations portent tout particulièrement sur l'acquisition d'une culture favorable à la recherche au SU, sur l'allègement le plus grand possible du fardeau de la collecte des données pour le personnel clinique par une conception minutieuse des outils de collecte de données et par le recours au personnel de recherche ainsi que sur les communications entre les chercheurs et le personnel clinique dans le but de favoriser le respect des protocoles d'étude.